Limited Correlation of Shotgun Metagenomics Following Host Depletion and Routine Diagnostics for Viruses and Bacteria in Low Concentrated Surrogate and Clinical Samples - Oechslin, Corinne P.; Lenz, Nicole; Liechti, Nicole; Ryter, Sarah; Agyeman, Philipp; Bruggmann, Rémy; Leib, Stephen L.; Beuret, Christian M. (Frontiers in Cellular and Infection Microbiology, 2018)
The etiologic cause of encephalitis, meningitis or meningo-encephalitis is unknown in up to 70% of cases. Clinical shotgun metagenomics combined with host depletion is a promising technique to identify infectious etiologies of central nervous system (CNS) infections. We developed a straightforward eukaryotic host nucleic acid depletion method that preserves intact viruses and bacteria for subsequent shotgun metagenomics screening of clinical samples, focusing on cerebrospinal fluid (CSF). A surrogate CSF sample for a CNS infection paradigm was used to evaluate the proposed depletion method consisting of selective host cell lysis, followed by enzymatic degradation of the liberated genomic DNA for final depletion with paramagnetic beads. Extractives were subjected to reverse transcription, followed by whole genome amplification and next generation sequencing. The effectiveness of the host depletion method was demonstrated in surrogate CSF samples spiked with three 1:100 dilutions of Influenza A H3N2 virus (qPCR Ct-values 20.7, 28.8, >42/negative). Compared to the native samples, host depletion increased the amount of the virus subtype reads by factor 7127 and 132, respectively, while in the qPCR negative sample zero vs. 31 (1.4E-4 %) virus subtype reads were detected (native vs. depleted). The workflow was applied to thirteen CSF samples of patients with meningo-/encephalitis (two bacterial, eleven viral etiologies), a serum of an Andes virus infection and a nose swab of a common cold patient. Unlike surrogate samples, host depletion of the thirteen human CSF samples and the nose swab did not result in more reads indicating presence of damaged pathogens due to, e.g. host immune response. Nevertheless, previously diagnosed pathogens in the human CSF samples (six viruses, two bacteria), the serum, and the nose swab (Human rhinovirus A31) were detected in the depleted and/or the native samples. Unbiased evaluation of the taxonomic profiles supported the diagnosed pathogen in two native CSF samples and the native and depleted serum and nose swab, while detecting various contaminations that interfered with pathogen identification at low concentration levels. In summary, damaged pathogens and contaminations complicated analysis and interpretation of clinical shotgun metagenomics data. Still, proper consideration of these issues may enable future application of metagenomics for clinical diagnostics.